Optical properties of silicon oxynitride films grown by plasma-enhanced chemical vapor deposition - Aschwanden, R.; Köthemann, R.; Albert, M.; Golla, C.; Meier, Cedrik (Thin Solid Films)
In this paper, silicon oxynitride films (SiON) grown by plasma-enhanced chemical vapor deposition are investigated. As precursor gases silane (SiH4), nitrous oxide (N2O), nitrogen (N2) and ammonia (NH3) are used with different compositions. We find that for achieving high nitrogen content adding ammonia to the precursor mix is most efficient. Moreover, we investigate the balance between adsorption and desorption processes during film growth by investigating the film growth rate as a function of the substrate temperature. From these data we are able to determine an effective activation energy for the film growth, corresponding to the difference between adsorption and desorption energy. Finally, we have thoroughly investigated the optical properties of the films using spectroscopic ellipsometry. From these measurements, we suggest a parametrized model for the refractive index and extinction coefficient in a wide range of compositions based on a Cauchy- and a Lorentz-fit.

Optical in-situ temperature management for high-quality ZnO molecular beam epitaxy - Albert, M.; Golla, C.; Meier, Cedrik (Journal of Crystal Growth)

Second harmonic generation on excitons in ZnO/(Zn,Mg)O quantum wells with built-in electric fields - Mund, Johannes; Yakovlev, Dmitri R.; Sadofev, Sergey; Meier, Cedrik; Bayer, Manfred (Physical Review B)

Nanoantennas embedded in zinc oxide for second harmonic generation enhancement - Volmert, Ruth; Weber, Nils; Meier, Cedrik (Journal of Applied Physics)
Plasmonic nanoantennas for visible and infrared radiation strongly improve the interaction of light with the matter on the nanoscale due to their strong near-field enhancement. In this study, we investigate a double-resonant plasmonic nanoantenna, which makes use of plasmonic field enhancement, enhanced outcoupling of second harmonic light, and resonant lattice effects. Using this design, we demonstrate how the efficiency of second harmonic generation can be increased significantly by fully embedding the nanoantennas into nonlinear dielectric material ZnO, instead of placing them on the surface. Investigating two different processes, we found that the best fabrication route is embedding the gold nanoantennas in ZnO using an MBE overgrowth process where a thin ZnO layer was deposited on nanoantennas fabricated on a ZnO substrate. In addition, second harmonic generation measurements show that the embedding leads to an enhancement compared to the emission of nanoantennas placed on the ZnO substrate surface. These promising results facilitate further research to determine the influence of the periodicity of the nanoantenna arrangement of the resulting SHG signal.

Zinc oxide based dielectric nanoantennas for efficient nonlinear frequency conversion - Golla, C.; Weber, N.; Meier, Cedrik (Journal of Applied Physics)

Strong nonlinear optical response from ZnO by coupled and lattice-matched nanoantennas - Protte, Maximilian; Weber, Nils; Golla, Christian; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

High-precision determination of silicon nanocrystals: optical spectroscopy versus electron microscopy - Köthemann, Ronja; Weber, Nils; Lindner, Jörg K N; Meier, Cedrik (Semiconductor Science and Technology)

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Tailored UV Emission by Nonlinear IR Excitation from ZnO Photonic Crystal Nanocavities - Hoffmann, Sandro P.; Albert, Maximilian; Weber, Nils; Sievers, Denis; Förstner, Jens; Zentgraf, Thomas; Meier, Cedrik (ACS Photonics)
Keywords: tet_topic_phc

Understanding band alignments in semiconductor heterostructures: Composition dependence and type-I–type-II transition of natural band offsets in nonpolar zinc-blendeAlxGa1−xN/AlyGa1−yNcomposites - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (Physical Review B)

Zn–VI quasiparticle gaps and optical spectra from many-body calculations - Riefer, Arthur; Weber, Nils; Mund, Johannes; Yakovlev, Dmitri R.; Bayer, Manfred; Schindlmayr, Arno; Meier, Cedrik; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)
The electronic band structures of hexagonal ZnO and cubic ZnS, ZnSe, and ZnTe compounds are determined within hybrid-density-functional theory and quasiparticle calculations. It is found that the band-edge energies calculated on the G0W0 (Zn chalcogenides) or GW (ZnO) level of theory agree well with experiment, while fully self-consistent QSGW calculations are required for the correct description of the Zn 3d bands. The quasiparticle band structures are used to calculate the linear response and second-harmonic-generation (SHG) spectra of the Zn–VI compounds. Excitonic effects in the optical absorption are accounted for within the Bethe–Salpeter approach. The calculated spectra are discussed in the context of previous experimental data and present SHG measurements for ZnO.

Time-resolved photon echoes from donor-bound excitons in ZnO epitaxial layers - Poltavtsev, S. V.; Kosarev, A. N.; Akimov, I. A.; Yakovlev, D. R.; Sadofev, S.; Puls, J.; Hoffmann, S. P.; Albert, M.; Meier, Cedrik; Meier, Torsten; Bayer, M. (Physical Review B)

Fabrication of fully undercut ZnO-based photonic crystal membranes with 3D optical confinement - Hoffmann, Sandro Phil; Albert, Maximilian; Meier, Cedrik (Superlattices and Microstructures)

Novel mechanisms of optical harmonic generation on excitons in semiconductors - Yakovlev, D. R.; Warkentin, W.; Brunne, D.; Mund, J.; Pavlov, V. V.; Rodina, A. V.; Pisarev, R. V.; Bayer, M. (Nonlinear Optics and Applications IX)

GaNm-plane: Atomic structure, surface bands, and optical response - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero; Neumann, M. D.; Speiser, E.; Esser, N. (Physical Review B)

IntrinsicLiNbO3point defects from hybrid density functional calculations - Li, Yanlu; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)